Hausgemachte Inflationsrisiken; Homemade inflation risks - Stefan Kooths (Wirtschaftsdienst, 2022)
– The COVID-19 pandemic massively interrupted economic activity all over the world. Governments responded by running huge fiscal deficits (financed via central banks) to support firms and consumers, thereby injecting purchasing power into the private sector on a large scale. With no corresponding production of goods and services, these phantom incomes are by their very nature inflationary. This explains the root cause of the post-pandemic price pressure. New fiscal programs created to compensate resulting losses of purchasing power only prolong the inflationary phase. Anchored inflation expectations are key to keeping the inflation process temporary. While this clearly falls under the responsibility of the monetary authorities, fiscal policymakers should support central banks by quickly ending the crisis mode. This is particularly important for the euro area where the problem of fiscal dominance would otherwise continue to increase.
Keywords: E31; E58; E65; 330; Inflation; Inflationsrate; Deutschland; Inflation; Inflationsrate; Deutschland